Extrafine inhaled triple therapy versus dual bronchodilator therapy in chronic obstructive pulmonary disease (TRIBUTE): a double-blind, parallel group, randomised controlled trial. Issue 10125 (17th March 2018) - Papi, Alberto; Vestbo, Jørgen; Fabbri, Leonardo; Corradi, Massimo; Prunier, Hélène; Cohuet, Géraldine; Guasconi, Alessandro; Montagna, Isabella; Vezzoli, Stefano; Petruzzelli, Stefano; Scuri, Mario; Roche, Nicolas; et al.
Summary: Background: Evidence is scarce on the relative risk-benefit of inhaled triple therapy, consisting of inhaled corticosteroid, long-acting muscarinic antagonist, and long-acting β2 -agonist, versus dual bronchodilation for chronic obstructive pulmonary disease (COPD). We aimed to compare a single-inhaler triple combination of beclometasone dipropionate, formoterol fumarate, and glycopyrronium (BDP/FF/G) versus a single-inhaler dual bronchodilator combination of indacaterol plus glycopyrronium (IND/GLY) in terms of the rate of moderate-to-severe COPD exacerbations over 52 weeks of treatment. Methods: This randomised, parallel-group, double-blind, double-dummy study was done at 187 sites across 17 countries. Eligible patients had symptomatic COPD, severe or very severe airflow limitation, at least one moderate or severe exacerbation in the previous year, and were receiving inhaled maintenance medication. After a 2 week run-in period with one inhalation per day of IND/GLY (85 μg/43 μg), patients were randomly assigned (1:1), via an interactive response technology system, to receive 52 weeks of treatment with two inhalations of extrafine BDP/FF/G (87 μg/5 μg/9 μg) twice per day or one inhalation of IND/GLY (85 μg/43 μg) per day. Randomisation was stratified by country and severity of airflow limitation. The primary endpoint was the rate of moderate-to-severe COPD exacerbations across 52 weeks of treatment in all randomised patients who received at least one dose of study drug and had at least one post-baseline efficacy assessment. Safety was assessed in all patients who received at least one dose of study drug. This study is registered withClinicalTrials.gov, numberNCT02579850 . Findings: Between May, 29 2015, and July 10, 2017, 1532 patients received BDP/FF/G (n=764) or IND/GLY (n=768). Moderate-to-severe exacerbation rates were 0·50 per patient per year (95% CI 0·45–0·57) for BDP/FF/G and 0·59 per patient per year (0·53–0·67) for IND/GLY, giving a rate ratio of 0·848 (0·723–0·995, p=0·043) in favour of BDP/FF/G. Adverse events were reported by 490 (64%) of 764 patients receiving BDP/FF/G and 516 (67%) of 768 patients receiving IND/GLY. Pneumonia occurred in 28 (4%) patients receiving BDP/FF/G versus 27 (4%) patients receiving IND/GLY. One treatment-related serious adverse event occurred in each group: dysuria in a patient receiving BDP/FF/G and atrial fibrillation in a patient receiving IND/GLY. Interpretation: In patients with symptomatic COPD, severe or very severe airflow limitation, and an exacerbation history despite maintenance therapy, extrafine BDP/FF/G significantly reduced the rate of moderate-to-severe exacerbations compared with IND/GLY, without increasing the risk of pneumonia. Funding: Chiesi Farmaceutici.